Indigenous Diplomacies - Beier, J. author. aut Link
XVI, 260 p.
Keywords: This volume explores broad conceptual questions raised by the 'discovery' of indigenous peoples as increasingly important global political actors - questions made all the more urgent by the sudden recognition that indigenous diplomacies are not at all new, but merely newly noticed.